2015
DOI: 10.1007/s11999-014-3757-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Morbidity and Mortality of Same-admission Staged Bilateral TKA

Abstract: Background Controversy continues regarding the optimal timing of surgery for patients with symptomatic bilateral degenerative knee arthritis who are not considered eligible for same-day bilateral TKA (BTKA). Questions/purposes We compared (1) 30-day mortality; (2) rates of in-hospital complications; and (3) blood transfusion rates between patients undergoing sameadmission staged BTKA and patients undergoing BTKA staged within 1 year in a highly specialized center where specific guidelines have been implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…[8][9][10] Although many studies have reported short-term mortality after TKA, many of them primarily compared the outcomes among unilateral TKA and simultaneous and staged bilateral TKAs. [11][12][13][14][15][16][17] However, several studies have analyzed mid-term or long-term patient survival after TKA. Based on those reports, rheumatoid arthritis (RA), 9 ,10,18,19 male sex, 9 ,10 age 9,10,19,20 , American Society of Anesthesiologist (ASA) grade, 19 ,21 body mass index (BMI), 19 diabetes, 8 and history of smoking 19 of patients undergoing TKA are reported to be linked to increased mortality in populations mainly from the US 8 and European countries.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Although many studies have reported short-term mortality after TKA, many of them primarily compared the outcomes among unilateral TKA and simultaneous and staged bilateral TKAs. [11][12][13][14][15][16][17] However, several studies have analyzed mid-term or long-term patient survival after TKA. Based on those reports, rheumatoid arthritis (RA), 9 ,10,18,19 male sex, 9 ,10 age 9,10,19,20 , American Society of Anesthesiologist (ASA) grade, 19 ,21 body mass index (BMI), 19 diabetes, 8 and history of smoking 19 of patients undergoing TKA are reported to be linked to increased mortality in populations mainly from the US 8 and European countries.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Poultsides et al. reported that the incidence of wound infection was 3 times higher in the simultaneous group than in the staged group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence about the efficacy and safety of staggered bilateral KA is very limited. According to a meta-analysis that compared the postoperative outcomes of staggered bilateral KA, simultaneous bilateral KA and staged bilateral KA, only five relevant articles were found and they offered conflicting results [ [16] , [17] , [18] , [19] , [20] ]. Two studies indicated that staggered bilateral KA had significantly superior outcomes than simultaneous bilateral KA [ 17 , 18 ], and one study suggested that staggered bilateral KA was correlated with more complications than simultaneous bilateral KA [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Staggered bilateral TKA is a surgical strategy wherein two procedures are performed on two different operative days within a 4–7‐day interval. This strategy has advantages over staged bilateral TKA, wherein two unilateral knee replacement arthroplasties are performed within 1 year at different hospitalization schedules [7]; that is, the surgery of both knees can be accomplished during a single hospitalization, thereby decreasing the overall recovery time and hospitalization for replacement of both knees [18]. However, a previous study showed that staggered bilateral TKA results in more acute post‐operative anaemia (11% vs. 3%) and blood transfusions (93% vs. 54%) compared with staged bilateral TKA [18].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has advantages over staged bilateral TKA, wherein two unilateral knee replacement arthroplasties are performed within 1 year at different hospitalization schedules [7]; that is, the surgery of both knees can be accomplished during a single hospitalization, thereby decreasing the overall recovery time and hospitalization for replacement of both knees [18]. However, a previous study showed that staggered bilateral TKA results in more acute post‐operative anaemia (11% vs. 3%) and blood transfusions (93% vs. 54%) compared with staged bilateral TKA [18]. The causes of post‐operative anaemia can be the presence of pre‐existing anaemia, surgical blood loss, and surgery‐related inflammation, which may blunt erythropoiesis for recovery.…”
Section: Discussionmentioning
confidence: 99%